2018
DOI: 10.1021/acs.est.7b05453
|View full text |Cite
|
Sign up to set email alerts
|

The Overlooked Occurrence of Environmentally Persistent Free Radicals in an Area with Low-Rank Coal Burning, Xuanwei, China

Abstract: The mining and burning of low-rank coal in Xuanwei, China have attracted a great deal of research attention because of the generated polyaromatic hydrocarbons (PAHs) and the high incidence of lung cancer in this region. Given the abundant transition metals in the allitic soil, we hypothesized that environmentally persistent free radicals (EPFRs) are formed in this region and the potential risk had not been addressed. Strong electron paramagnetic resonance (EPR) signals of 3.20 × 10 - 3.10 × 10 spins/g were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 51 publications
4
45
2
Order By: Relevance
“…Thus far, we have reported data of EPFRs in airborne PM in six countries, i.e., China, Germany, Greece, India, Saudi Arabia and the USA. As listed in Table 1, there are various forms of sampling media for airborne PM, including a glass fiber filter (GFF) [21,31], quartz fiber filter (QFF) [32][33][34][35], Teflon membrane filter (TMF) [24,36,37], polytetrafluoroethylene (PTFE) [35,38,39], polycarbonate filter (PCF) [40], and even a leaf [41].…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, we have reported data of EPFRs in airborne PM in six countries, i.e., China, Germany, Greece, India, Saudi Arabia and the USA. As listed in Table 1, there are various forms of sampling media for airborne PM, including a glass fiber filter (GFF) [21,31], quartz fiber filter (QFF) [32][33][34][35], Teflon membrane filter (TMF) [24,36,37], polytetrafluoroethylene (PTFE) [35,38,39], polycarbonate filter (PCF) [40], and even a leaf [41].…”
Section: Samplingmentioning
confidence: 99%
“…If the aim is to obtain the overall content of EPFRs in the PM sample, it is advisable to use the QTB or QSB method. Studies have shown that most of the EPFRs in airborne PM are derived from solvent-resistant organic matter [21,45,46]. For instance, the direct measurement using the QSB method yielded an average EPFR concentration of 3.97 × 10 14 spins/m 3 for 12 samples collected in December 2017 in Xi'an, China.…”
Section: Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, environmentally persistent free radicals (EPFRs) have attracted increasing attentions in respect of their adverse impacts on health (Lomnicki et al, 2008;Wang et al, 2018). EPFRs are formed during the pyrolysis of biomass in the presence of metal oxides via a mechanism of chemisorption followed by electron transfer (Lomnicki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Coal with higher volatile matter contributed to higher toxicity (cytotoxicity and global DNA methylation) in coal combustion particles produced by residential stoves (Wang et al 2016a). Hydroxyl radical generation of coal combustion particles collected from the chimney of coal power plant was much higher than total suspended particles in the ambient atmosphere (Wang et al 2018). However, the effects of coal burning temperature on both the chemistry and toxicity of coal combustion particles have not been adequately reported.…”
Section: Introductionmentioning
confidence: 97%